MINIMALISASI STUNTING DAN DETEKSI DINI MASALAH PERKEMBANGAN BALITA DI POSYANDU 2 DESA ARANGMANGU KECAMATAN PURWOJATI BANYUMAS - Linda Yanti; Surtiningsih (LPPM UMRI, 2019)
Banyumas Regency is ranked in the top 100 districts with the highest stunting rates in Indonesia. The stunting rate in Banyumas is known to be 24% of the 300 under-five samples, the number has exceeded the WHO standard, which is a maximum of 20%. In Karangmangu Village based on the results of a preliminary survey in Posyandu 2 Karangmangu of 30 toddlers who carried out weighing in Posyandu 2 found that 5 children were stunted and 2 were malnourished. Based on preliminary data at Posyandu 2, it is necessary to make a comprehensive approach especially for babies under the age of 2 years (Baduta). Early detection of malnutrition status and stunting is expected to be handled properly so as to minimize problems that can arise from malnutrition and stunting problems. The activities that will be carried out include a thorough assessment, examination of growth and development, examination of motor development, training in appetite massage for infants / toddlers, provision of vitamin A and supplementation of milk for toddlers with malnutrition and stunting. The results of this activity were the detection of cases of malnutrition and stunting of infants under 2 years of age (Baduta) in Karangmangu Village, assisting Baduta with counseling about stunting and malnutrition, training in cold cough massage and appetite massage, vitamin A supplementation and supplementary food at each meeting, as well as providing additional milk for infants of poor nutritional status and stunting of 15 under two toddlers.